Positive Values Of The Malays In Malay Poems (Pantun) - Ariffin, Norita (2006)

(untitled)
This research is carried out to look at the positive values of the Malays which are found in the compilation of Malay poems (pantun) from a book, Bingkisan Permata published by Yayasan Karyawan in the year 2001. In analyzing these poems, the researcher uses the approach of Malay Methodology (Teori Pengkaedahan Melayu) by Hashim Awang. The objective of this study is to look at the positive values practiced by the traditional Malay community which is portrayed through the poems. This research concentrates on the nine key-values practiced by the traditional Malay community. These values include good heartedness, integrity, respectfulness, compassion, honesty, cooperativeness, thankfulness and courage. These values encompass the aspects of morality, believes, education, gratitude, honour and the positive outlook on life.Based on the result of research, it can be concluded that almost all poems (pantun) potray positive values that are applied directly or indirectly through attractive word chosen. Its potrayal displays aesthetic values or beauty that encompass elements of positive values which reflect the culture of the Malay society. This indicates that poems being analyzed are the result of arts literature projecting the identity of its society. The most dominant value potrayed in the poem being analyzed is compassion. The result of this study shows that the positive values used in this research are in line with earlier researches that has been done by academics and historians on the related subjects. This research which uses the Theory of Malay Methodology, focuses on the moral approach, the societal approach, the artistic approach and the religious approach. The particular technique employed proves the existence of positive values in the poems. The result of this study enable a clear portrayal of Malay society values in their poems (pantun).